Asset poverty in the United States: Its persistence in an expansionary economy - Asena Caner; Edward N. Wolff (Levy Economics Institute of Bard College, 2004)
Economic growth and a rising stock market in the 1990s gave the impression that everyone was accumulating wealth and asset poverty rates were declining. The impression was supported by the official, income-based poverty measure, which exhibited a sharp decline. According to Senior Scholar Edward N. Wolff and Research Scholar Asena Caner, poverty measures should include wealth as well as income. Their study of asset poverty in the United States between 1984 and 1999 focuses on the lower end of the wealth distribution and shows that asset poverty rates did not decline during the period studied, and that the severity of poverty increased. It also shows that asset poverty is much more persistent than income poverty.
Keywords: 330; Armut; Vermögen; Schätzung; USA